1964
DOI: 10.1192/bjp.110.469.800
|View full text |Cite
|
Sign up to set email alerts
|

Short Courses of E.C.T. and Simulated E.C.T. in Chronic Schizophrenia

Abstract: The problem of treating the “back ward” chronic schizophrenic is likely to remain for some years to come, and with it the problem of establishing the genuine effectiveness of particular treatments. Disentangling effective from non-effective therapeutic techniques in “total-push” programmes is particularly complicated. What precisely is responsible for the minimal improvements observed: some subtle change in “ward climate”, the altered medication or the new music therapist? Writers who view mental illness prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…In a study published in 1959, Brill et al39 treated 67 male patients with chronic schizophrenia with ECT or pentothal alone. In a third study published in 1964, Heath et al40 compared ECT to sham ECT involving pentothal anesthesia alone in 45 patients with chronic schizophrenia. None of these studies found any appreciable differences between treatment groups in clinical outcome.…”
Section: Overview Of Efficacy Researchmentioning
confidence: 99%
“…In a study published in 1959, Brill et al39 treated 67 male patients with chronic schizophrenia with ECT or pentothal alone. In a third study published in 1964, Heath et al40 compared ECT to sham ECT involving pentothal anesthesia alone in 45 patients with chronic schizophrenia. None of these studies found any appreciable differences between treatment groups in clinical outcome.…”
Section: Overview Of Efficacy Researchmentioning
confidence: 99%
“…Another aspect of the literature has been real versus sham ECT studies. In general terms, pre 1980 studies failed to show an advantage for ECT 4–6 whereas later studies show substantial advantage in short‐term therapeutic outcome 7–9 . Factors likely to account for this include the chronicity of patients studied (unremitting chronic patients in the older studies, compared to the greater inclusion of patients with acute exacerbations in the newer studies) and the use of concomitant antipsychotic medication (in the newer studies, both in the sham and the ECT groups) 3…”
Section: Efficacy: What Does the Literature Say?mentioning
confidence: 99%
“…Among the early studies, only one found a therapeutic advantage for ECT [49], the others did not [43,[50][51][52][53]. Three sham ECT-controlled studies in the 1980s suggested short-lived clinical benefits [54][55][56], but these studies were also methodological flawed.…”
Section: Previous Studies On the Efficacy Of Ectmentioning
confidence: 93%